2023
DOI: 10.21203/rs.3.rs-2360630/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research on the Content of Plumbago auriculata (L.) Hairy Roots Mediated by Agrobacterium Rhizogenes and Its Plumbagin

Abstract: Agrobacterium rhizogene-mediated genetic transformation of hairy roots is an effective method to obtain secondary metabolites. In accordance with different genotypes, it is very specific and difficult to set up a stable genetic transformation system. The plumbagin is found in the roots of Plumbago auriculata L., a secondary metabolite with significant medicinal value, but the common root grows slowly, its accumulation period is lengthy (2–6 years). In this paper, we first explored the most effective A. rhizoge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Hairy roots were induced in Entada strains in Tribulus terrestris to stimulate hairy roots showed that strain 15834 performed better(Shara et al 2013).A complicated issue in hairy root related studies is that the results differ for species inside the same family and genus, limiting the selection of effective strains in different plant genotypes. For example, strain ATCC 15834 in Plumbago auriculata(Zian et al 2023), but strain LBA9402 in Plumbago paniculata, showed the best hairy root induction e ciency(Nayak et al 2015). Moreover, strains ATCC 15834 and ATCC 13333 in Capsicum frutescens and strains ATCC 43056 and ATCC 43057 in Capsicum annuum, had a better induction effect (MdSetamam et al 2014).The e ciency of bacterial strains can be attributed to the difference in the degree of pathogenicity of these strains, the expression patterns of Ri (T-DNA) genes, and the random integration of T-DNA in the host genome(Bansal et al.…”
mentioning
confidence: 99%
“…Hairy roots were induced in Entada strains in Tribulus terrestris to stimulate hairy roots showed that strain 15834 performed better(Shara et al 2013).A complicated issue in hairy root related studies is that the results differ for species inside the same family and genus, limiting the selection of effective strains in different plant genotypes. For example, strain ATCC 15834 in Plumbago auriculata(Zian et al 2023), but strain LBA9402 in Plumbago paniculata, showed the best hairy root induction e ciency(Nayak et al 2015). Moreover, strains ATCC 15834 and ATCC 13333 in Capsicum frutescens and strains ATCC 43056 and ATCC 43057 in Capsicum annuum, had a better induction effect (MdSetamam et al 2014).The e ciency of bacterial strains can be attributed to the difference in the degree of pathogenicity of these strains, the expression patterns of Ri (T-DNA) genes, and the random integration of T-DNA in the host genome(Bansal et al.…”
mentioning
confidence: 99%